Methods for Research in an Approach to the Standpoint of the Subject - Ittner, Helmut (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2016)
Empirical research which is based on "critical psychology" (HOLZKAMP, 1985) may allow a productive access to and ways to deal with the obstinacy of subjective grounds for action. This is particularly interesting for research on learning or educational processes. Little work has been done to provide adequate analysis of the subject's perspective relating to the paradigm of critical psychology. In the present contribution a way is suggested using procedures of the "documentary method" (BOHNSACK, 2014) and principles of "situational analysis" (CLARKE & KELLER, 2012) to construct a suitable set of methods. The approach is based on the assumption that it is necessary to question concrete analysis methods in view of their suitability for a research regarding the standpoint of the subject and to justify an application of the defined methods. The data discussed were collected in a research project on the learning strategies in an adult education program. URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs1602106